ANALISIS KOMPARASI RASIO PROFITABILITAS BANK BUMN SEBELUM DAN SAAT ADANYA PANDEMI COVID-19 TAHUN 2019-2020 - Niu, Fitria Ayu Lestari; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2021)
This study aims to determine the significant differences in the profitability ratios of BUMN banks before and during the 2019-2020 pandemic of covid-19 using quantitative methods. The population in this study was 32 data with secondary data types in the form of financial statements of Bank Rakyat Indonesia, Bank Negara Indonesia, Bank Mandiri and Bank Tabungan Negara per quarter during 2019 and 2020 and processed using the Paired samples test. The results of this study found that there were significant differences in profitability analyzed from ROA, ROE and BOPO at BUMN Banks before and during the Covid-19 pandemic with the results of ROA analysis that these four BUMN banks increased financing or providing credit to third parties by increasing their loss reserves in 2020. In the ROE analysis, all BUMN Bank experienced an increase in the number of liabilities that were not used to increase the amount of equity held by the Bank, but were used and allocated for loss reserves as mandated by Otoritas Jasa Keuangan in dealing with problems and risks that occurred during the covid-19 pandemic and from the BOPO analysis found that BRI, BNI, Mandiri and BTN increased the recovery of the estimated loss on commitments and contingencies as well as the decline in the value of productive assets during the covid-19 pandemic.